A CORRUPTION AND UNDERDEVELOPMENT AS GEARED BY BUREAUCRATS IN NIGERIA - Alfakoro, Abubakar S. Yushau (Journal of Advanced Research in Public Policy and Administration, 2020)
Theories abound for the different possible causes of the flagrant graft that exists in Nigeria, some blame greed and ostentatious lifestyle as a potential root cause of corruption. Nigeria is faced with problems where funds meant for implementation of developmental project are siphoned, civil service ethics are declining and meritocracy is lost for personal regarding interest by public bureaucrats all in the name of corruption, this study however focus on the researchers attempt to study how corruption in public bureaucracy can be curtailed. It is no denying fact that the bureaucrats is an integral component of societal development in developed countries of the world but has been converted to an engineer or architect of corruption in our darling Nigeria. The study discovers that dismality in neutrality; integrity and ethics in public bureaucracy required for the success in the discharging out of public duties are lost. This has happened, despite many governmental agencies and policies created to check corruption proves counterproductive, this paper recommends a reform of the system and process to enhance development because corruption is a fundamental component of injustice and no society will progress or develop if it bureaucrats are corrupt and mischievous, and no society progresses with corrupt leaders as custodian.